USOS Y FUNCIONES DE (I)DIAY EN COSTA RICA Mario Hernández Delgado - Hernández Delgado, Mario (2012)
In this communication we try to make a systematized revision of the main uses and functions of the expression (i) diay in Costa Rica. In this country it seems to be perceived as a very characteristic linguistic element of their cultural identity. Based on the revision of the descriptions that appear in different works, mainly of lexicographic kind, it is suggested the need to try a more precise and updated lexicographic characterization that includes its effective uses, indication of its variants and good contextual examples. The main functions that will be mentioned (not all of them clearly reflected in the lexicographic works) are: conversational marker, interjective/exclamative and interrogative functions. These functions allow diverse uses, as it will be detailed. It is concluded that the term (i)diay is in Costa Rican Spanish a highly desemantized element regarding its historic origin (< y de ahí). In addition, it seems that it has been partially semantized again and only for certain uses, besides it has also been gramaticalized in a very restricted way. These characteristics that make it so flexible and adaptable to several discursive uses and pragmatic interpretations seem to be precisely the ones that justify that it has been integrated and maintained in the Costa Rican linguistic communication system.